Translating the Cover – A Comparative Study of the Covers of Arabic Novels and Their English Translations - Lovisa BERG (transLogos: Translation Studies Journal, 2022)
Translation studies have traditionally focused on the textual aspects of a work. This article, instead, concentrates on the multimodal translation practices involved in the translation of covers. When a novel is introduced to another linguistic and cultural sphere, its cover and paratext usually change. The cover is one of the prime factors that influence the first view of a literary work. This article applies content analysis to examine the specific features of the cover imagery and design of 55 contemporary Arabic novels and compare them with the covers of their English translations. The comparison is based on paratextual features such as position of the title and author’s name as well as content-based elements like the selection of cover motive and cultural aspects of that choice. The analysis shows that there are significant differences between the Arabic and English covers regarding color, motive, and design and that whereas the Arabic novels often carry signifiers of a clear cultural identity, that is not the case with the English translations of the same novels. The translated covers are shown to be domesticated versions that are appealing to the target culture, using target culture aesthetics, rather than clear representatives of the source culture.